Adhesion-Deformation-Hydrodynamic model of friction and wear - Stelmakh, Oleksandr; Fu, Hongyu; Guo, Yiqiao; Wang, Xinbo; Zhang, Hao; Dykha, Oleksandr (Problems of Tribology, 2022)
The proposed Adhesion-Deformation-Hydrodynamic model of friction and wear is based on the relationship of elastic-deformation processes in the surfaces of curvilinear contacts with hydrodynamic regular processes of extrusion and rarefaction in lubricating layers in tribocontacts, as well as with the processes of primary adhesion of friction surfaces and subsequent acts of adhesive wear. The proposed Adhesion-Deformation-Hydrodynamic model of friction and wear and its main provisions on the relationship between extrusion, rarefaction in lubricating layers and primary adhesion of friction surfaces of curvilinear contacts cover the entire load-speed range and all modes of lubrication of friction surfaces